Design and Implementation of Web-Based IT Helpdesk Ticketing System to Improve Client Issue Manageme at PT. Good and Service Solutions - Raihan Ali Najmi; Aji Puspito Nugroho; Muhammad Rizqi; Wasis Haryono (Journal of Research and Publication Innovation, 2025)
In the rapidly evolving digital era, efficient and effective information technology services are crucial for companies across various sectors. This paper presents the design and implementation of a web-based IT Helpdesk Ticketing System using the Laravel framework at PT Good and Service Solutions. The existing manual system faced challenges such as delayed responses, difficulty in tracking requests, and lack of visibility into support team performance. The proposed system automates and optimizes the issue management process, allowing for better tracking and reporting of client requests. Key features include ticket management, status tracking, and performance analytics. The implementation of this system is expected to enhance operational efficiency, reduce response times, and improve client satisfaction. The findings indicate that the new system significantly streamlines the support process, providing a structured approach to managing IT issues. Future enhancements may include advanced analytics and security features to further improve system performance.